Evaluation and Multivariate Analysis of Cowpea [Vigna unguiculata (L.) Walp] Germplasm for Selected Nutrients—Mining for Nutri-Dense Accessions - Padhi, Siddhant Ranjan; Bartwal, Arti; John, Racheal; Tripathi, Kuldeep; Gupta, Kavita; Wankhede, Dhammaprakash Pandhari; Mishra, Gyan Prakash; Kumar, Sanjeev; Archak, Sunil; Bhardwaj, Rakesh (Frontiers in Sustainable Food Systems, 2022)
120 highly diverse cowpea (Vigna unguiculata (L.) Walp) genotypes, including indigenous and exotic lines, were evaluated for different biochemical traits using AOAC official methods and other standard methods. The results exhibited wide variability for protein, ranging from 19.4-27.9%, starch and amylose ranged from 27.5-42.7 g.100g-1 and 9.65 - 21.7 g.100g-1 respectively, while TDF & TSS ranged from 13.7- 21.1 g.100g-1 and 1.30-8.73 g.100g-1 respectively. Anti-nutritional factors like phenols and phytic acid ranged from 0.026-0.832 g.100g-1 & 0.690-1.88 g.100g-1 respectively. The correlation coefficient between traits was calculated to understand the inter-trait relationship. Multivariate analysis (PCA & HCA) was performed to identify major traits contributing to variability and group accessions with a similar profile. First three principal components, i.e., PC1, PC2 & PC3, contributed to 62.7% of the variation, where maximum loadings were from starch, followed by protein, phytic acid, and dietary fiber. HCA formed six distinct clusters at a squared Euclidean distance of 5. Accessions in cluster I had high TDF and low TSS, while cluster II was characterized by low amylose. Accessions in cluster III had high starch, low protein, and phytic acid, whereas accessions in cluster IV contained high TSS, phenol, and low phytic acid. Cluster V is characterized by high protein, phytic acid, TSS, phenols, and low starch, and cluster VI had a high amount of amylose and low phenol content. Some nutri-dense accessions were identified from the above clusters like EC170579 and EC201086 with high protein (> 27%), TSS, amylose, and TDF. These compositions are promising to provide practical support for developing high-value food and feed varieties using effective breeding strategies with higher economic value.